Peaks and passion: Examining the dynamics of workplace commitments among outdoor sport guides - Fecker, Denise (Journal of outdoor recreation and tourism, 2025)
Outdoor sport and recreation organizations are key service providers in tourism, with their staff serving as their most valuable asset; however, while studies have explored employee retention in tourism service contexts, such as hotels and restaurants, research on employee commitment of outdoor sport guides is limited. This study examines the role of four different workplace commitments and their antecedents for the first time in the context of outdoor service providers in the tourism sector. Using a quantitative design, an online survey was conducted with 200 snowsport instructors in one of Austria's largest winter tourism destinations. Structural equation modeling was applied with SmartPLS 4.0 to test the hypotheses. This study's findings show that workplace commitments of outdoor sport guides are interrelated, and their explanations vary across the targets. Place attachment, camaraderie, meaningful work, and perceived organizational support significantly predict different workplace commitments. The results suggest that workplace commitments vary in their outcomes and highlight the roles of destinations and their stakeholders in employee retention and work outcomes within tourism and outdoor recreation sectors. This study establishes a workplace commitment framework that provides nuanced insights into the different emotional bonds of outdoor sport guides as a specific group of service workers in tourism.